Effekten av Bisfenol A (BPA) på hanråttors (Rattus norvegicus) reproduktion - Lindell, Malin (2015)
Today evidence exist that environmental chemicals deteriorate male sperm quality and that testicular cancer is increasing. Bisphenol A (BPA) is a chemical with estrogenic effects used in the manufacture of polycarbonate plastic and are found in, for instance, plastic boxes, feeding bottles and food containers. Much of the research on how men's reproductive ability is influenced are performed on rats. This review article complies how male rat reproduction is affected by BPA as a model for humans. Studies have investigated how sperm are affected, hormonal changes during reproduction and how reactive oxygen species (ROS) affects sperm. The results show that sperm quality and sperm motility is deteriorating if rats are exposed to BPA. The negative feedback regulation of testosterone decrease, leading to an increase of luteinizing hormone (LH), which in turn leads to a decrease of testicular function. A decrease of LH is also found that indicate a decrease of pituitary secretion of LH. Increased ROS production after exposure to BPA is making sperm unable to protect themselves and they end up in oxidative stress. Thus, there is evidence that male rats have an impaired fertility caused by exposure to BPA. Through further research the effects of BPA can be clarified in more detail, give us a better understanding of how BPA can cause deterioration of sperm quality and if there is a link to the increase in testicular cancer that is seen in humans.